Media Qualities and Preferences in Da'wah among Muslim Converts in Borneo. - Salinayanti, Salim (Universiti Kebangsaan Malaysia, 2021)
This comparative study attempts to investigate the media platforms preferred by Muslim converts in Borneo in receiving da’wah. The media involved in the comparison is of traditional media such as television, radio, book and newspaper, and of social media such as Facebook, YouTube, website and blog. The qualitative research methodology was used and a semi-structured interview was applied to collect the data from the informant. There were 42 Muslim converts who participated in this study as informants. The data obtained from the interview was tabulated using thematic approach, which later analysed using descriptive and interpretive phenomenology approach. The results revealed the most informants preferred traditional media platforms to learn more about Islam. This is an interesting finding because even the younger informants also opted for traditional media. Nevertheless, social media has its function in the informants’ lives in the search of more understanding about the religion they embraced